Estimation of Influence of Supply Network Power and Parameters of «Frequency Converter - Asynchronous Motor» System on Harmonic Spectrum of Its Discontinuous Input Current - B. I. Firago; K. M. Medvedev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The purpose of the paper is to investigate dependence of input current harmonic spectrum of modern frequency converters with uncontrolled rectifiers on supply network power , rated power and motor load, and also the DC filter capacity. Results of the investigations are given in the form of the corresponding dependencies and an estimation of correspondence of higher current harmonic levels generated by a frequency converter to the existing state standard.